2017
DOI: 10.1016/j.hydromet.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the application of chelating resins for rare earth recovery

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…Strong-acid cation exchange resins show higher affinity for metal cations of higher charge . This is because their adsorption affinity is determined mainly by the valence of the metal cation (Page, et al, 2017). Unlike the weak-base anion exchange resins, strong-acid cation exchange resins have no complexing ability (Zagorodni, 2007).…”
Section: For Instance Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong-acid cation exchange resins show higher affinity for metal cations of higher charge . This is because their adsorption affinity is determined mainly by the valence of the metal cation (Page, et al, 2017). Unlike the weak-base anion exchange resins, strong-acid cation exchange resins have no complexing ability (Zagorodni, 2007).…”
Section: For Instance Inmentioning
confidence: 99%
“…Unlike the weak-base anion exchange resins, strong-acid cation exchange resins have no complexing ability (Zagorodni, 2007). It is thus suggested that sulfate complexation of Th(IV) ions may have affected their adsorption affinity for strong-acid cation exchange resins (Borai & Mady, 2002;Page, et al, 2017). This is likely because Th(IV) ions, due to sulfate complexation, can exist as ThSO 4 2+ ions in a H 2 SO 4 system (Kim & Osseo-Asare, 2012).…”
Section: For Instance Inmentioning
confidence: 99%
“…HCl and chlorine are among the most effective leachants in the treatment of ores and materials containing metals [6]. Ion-exchange is a suitable technique to extract REEs from leach liquors [7], for instance by polyacrylate anion-exchanger resin (Amberlite IRA 958) [8], chemically modified Amberlite XAD-4 [9], as well as resins containing mixed sulfonic/phosphonic, amino-phosphonic or iminodiacetic acid functional groups [10]. Bioleaching is an environmentally-friendly technique whose results are still scant: the maximum REE leaching yield was 49%, achieved by Gluconobacter oxydans, that mainly synthesizes gluconic acid [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides selective precipitation [18], the most used technique for extraction and the further refining of REs from leach liquors is solvent extraction [18][19][20]. Ion-exchange is another hydrometallurgical technique that was used to extract REEs from leach liquors [21][22][23][24]. Bioleaching was also investigated to obtain an environmentally friendly process [25].…”
Section: Introductionmentioning
confidence: 99%